1991
DOI: 10.1063/1.350254
|View full text |Cite
|
Sign up to set email alerts
|

Electron-acoustic phonon scattering in SiO2 determined from a pseudo-potential for energies of EE BZ

Abstract: The existing description of hot electron transport in silicon dioxide contains the deficiency that the resulting electron inverse mean free paths and loss rates associated with electron-acoustic phonon scattering continue to increase in an unphysical way at energies above Egap. One can remove that discrepancy by introducing a pseudo-potential which reflects the screened atom characteristic of higher energy electron-lattice interactions. The low energy, low q scattering, described in terms of the deformation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…The electron thermalization time increases roughly inversely with optical phonon frequency, and was found to be about 7 ps in CsI, 2 ps in NaI, and 0.5 ps in CaF 2 16. Assuming a hot‐electron velocity distribution given by a parabolic band‐edge effective mass model in the first Brillouin zone, with approximate corrections applied in outer zones 5, 20, 21, the resulting step size and thermalization time yielded the hot‐electron ranges mentioned above 5, 16. This dramatic difference between the hot‐electron thermalization range and the restricted range of self‐trapped holes produces charge separation such as discussed in the thermalized model above, but substantially more because the hot‐electron diffusion is less sensitive to electric field attraction toward the track core of self‐trapped holes.…”
Section: Discussionmentioning
confidence: 99%
“…The electron thermalization time increases roughly inversely with optical phonon frequency, and was found to be about 7 ps in CsI, 2 ps in NaI, and 0.5 ps in CaF 2 16. Assuming a hot‐electron velocity distribution given by a parabolic band‐edge effective mass model in the first Brillouin zone, with approximate corrections applied in outer zones 5, 20, 21, the resulting step size and thermalization time yielded the hot‐electron ranges mentioned above 5, 16. This dramatic difference between the hot‐electron thermalization range and the restricted range of self‐trapped holes produces charge separation such as discussed in the thermalized model above, but substantially more because the hot‐electron diffusion is less sensitive to electric field attraction toward the track core of self‐trapped holes.…”
Section: Discussionmentioning
confidence: 99%
“…first introduced by Bradford and Woolf, 40 in which α is the screening correction factor, was added into the integrand of the acoustic phonon-particle scattering rate described by Sparks et al 36 to correct for the fact that the calculated scattering rates become unphysical as the particle energy increases beyond the energy of the first Brillouin zone. We used the same approach used by Bradford and Woolf to determine the value of α, i.e.…”
Section: Electron/hole Scattering Rates and Angles From Phononsmentioning
confidence: 99%
“…It has long been speculated that this would necessitate a full quantum description of the transport process. Alternatively, Bradford and Woolf [12] showed that the introduction of screening into the electron-acoustic-phonon interaction could reproduce the photoemission data quantitatively, without abandoning the semiclassical formalism. In this Letter we shall demonstrate experimentally that the discrepancy between the semiclassical Monte Carlo model and the photoemission results at kinetic energies > 6 eV is far more serious than a discrepancy in specific rates.…”
mentioning
confidence: 98%